THE ESTABLISHMENT OF THE SERBIAN SECRET SELF-DEFENSE ORGANIZATION IN METOHIJA AND KOSOVO AND THE VELIKA HOČA BATTLE 1905. (Heritage, 2025)
The paper examines the attempt to establish a secret self-defense organization of the Serbs in the Kosovo Pomoravlje, Sirinić, Kosovo, and Metohija during 1904–1905. The organization was based on arming the population, forming clandestine detachments, and creating channels for transferring weapons from the Serbian–Ottoman border across the Šar Mountains and the area around Tetovo, to Serbian-declared regions across the Vardar, into Poreče and the vicinity of Kičevo.                                                                                                                                                                 The adventurer and former hajduk Savatije Milošević, an employee of the Serbian consulates in Bitola and Priština, was entrusted with the task of creating the organization. Relying on his old connections with Albanians in Metohija, the organization he had established, and the fact that his associate Lazar Kujundžić was a native of Orahovac, Milošević attempted to lead a detachment and a shipment of weapons across Kosovo and Metohija to the Kičevo area. The seven-member Serbian detachment clashed with Ottoman troops and local Albanians in Velika Hoča, where it was annihilated to the last man.                                                                                                                  The destruction of the detachment led to the enclave-like isolation of the Serbs in Orahovac and Velika Hoča and their suffering, as well as to Albanian assaults on the Serbs and violent searches for weapons among Serbian communities in Kosovo and Metohija.
Keywords: Old Serbia, Serbian Chetniks, Ottoman Empire, Kosovo and Metohija, Velika Hoča, Orahovac